Los hombres de Dostoievski. - Víquez Jiménez, Alí (2012)
This article describes the philosophical base on which the principle characters of Dostoyevsky are created, with the understanding that they are constructed through a metaphysical platform that later has ethical consequences and -on occasion political ones-. The intent is to demonstrate how Dostoyevsky condemns to failure those who abandon their belief in God and how the only method of salvation that is offered to them consists of a return to their faith. It is first of three articles which have given rise to an investigation centered on three great novels of the Russian author: Crime and Punishment, The Possessed and The Brothers Karamazov.